Abnormal Functional Connectivity of Hippocampal Subdivisions in Obstructive Sleep Apnea: A Resting-State Functional Magnetic Resonance Imaging Study - Liu, Xiang; Chen, Liting; Duan, Wenfeng; Li, Haijun; Kong, Linghong; Shu, Yongqiang; Li, Panmei; Li, Kunyao; Xie, Wei; Zeng, Yaping; Peng, Dechang (Frontiers in Neuroscience, 2022)
The hippocampus is involved in memory and other cognitive functions. Hippocampal structural and functional abnormalities have been observed in patients with obstructive sleep apnoea (OSA), but the functional connection patterns among hippocampal subdivisions in this type of patients remain unclear. The purpose of this study was to investigate the changes in functional connectivity (FC) between hippocampal subdivisions and their relationship with neurocognitive function in male patients with OSA. Resting-state data were obtained from 46 male patients with untreated severe OSA and 46 male good sleepers. The hippocampus was divided into anterior, middle, and posterior parts, and differences of FC between hippocampal subdivisions and other brain regions were determined. Correlation analysis was used to explore relationships between abnormal FC of hippocampal subdivisions and clinical characteristics in patients with OSA. Our result revealed an increased FC in the OSA group between the left anterior hippocampus and left middle temporal gyrus; between the left middle hippocampus and the left inferior frontal gyrus, right anterior central gyrus, and left anterior central gyrus; between the left posterior hippocampus and right middle frontal gyrus; between the right middle hippocampus and left inferior frontal gyrus; and between the right posterior hippocampus and left middle frontal gyrus. These FC abnormalities were mainly manifested in the sensorimotor network, fronto-parietal network, and semantic control network, which are closely related to the neurocognitive impairment of OSA patients. This study advances the exploration of the potential pathophysiological mechanism of neurocognitive dysfunction in OSA.